Conversion Efficiency Improvement in GaAs Solar Cells - Das, Narottam; Islam, Syed (Springer, 2014)
The finite-difference time domain (FDTD) tool is used to simulate the reflection losses of subwavelength grating (SWG) structure in GaAs solar cells. The SWG structures act as an excellent alternative antireflective (AR) coating due to its capacity to reduce the reflection losses in GaAs solar cells. The SWG structures allow the gradual change in refractive index that confirms an excellent AR coating and light trapping properties, when compared with the planar thin film structures. The nanorod (nano-grating) structure acts as a single layer AR coating, whereas the triangular (conical or perfect cone) and parabolic (i.e., trapezoidal or truncated cone) shaped nano-grating structures act as a multilayer AR coating. The simulation results show that the reflection loss of triangular (conical or perfect cone) shaped nano-grating structure having a 300 nm grating height and an 830 nm period is ~2 %, which is about 28 % less than that of flat type substrates. The simulated results show that the light reflection of a rectangular shaped grating structure is ~30 %, however, the light reflection becomes ~2 % for a triangular (conical or perfect cone) shaped nano-grating structure, because the refractive index changes gradually in several steps and reduces the reflection losses. It is also noticed that the intermediate structures (trapezoidal and parabolic shaped), the light reflection loss is lower than the rectangular shaped nano-grating structure but higher than the triangular shaped nano-grating structure. The simulated results confirm that the reduction of light reflection losses in GaAs solar cell will increase the conversion efficiency. Therefore, this analysis confirmed that the triangular (i.e., perfect cone or conical) shaped nano-grating structures are an excellent alternative AR coating for the improvement of conversion efficiency in GaAs solar cells.